2021
DOI: 10.3390/biom11081216
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization Effect of Intrinsically Disordered Regions on Multidomain Proteins: The Case of the Methyl-CpG Protein 2, MeCP2

Abstract: Intrinsic disorder plays an important functional role in proteins. Disordered regions are linked to posttranslational modifications, conformational switching, extra/intracellular trafficking, and allosteric control, among other phenomena. Disorder provides proteins with enhanced plasticity, resulting in a dynamic protein conformational/functional landscape, with well-structured and disordered regions displaying reciprocal, interdependent features. Although lacking well-defined conformation, disordered regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…It has become clear that protein interaction and stability depend on context including regions outside of the “canonical” binding site. ,,, Emerging quantitative data suggest a role of disordered flanking regions, which could make multiple transient interactions with a folded interaction partner to either increase or decrease affinity. ,, Phylogenetic methods are powerful in pinpointing evolutionarily conserved regions in proteins. If these regions are involved in a protein–protein interaction, then the conserved residues are likely important for affinity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…It has become clear that protein interaction and stability depend on context including regions outside of the “canonical” binding site. ,,, Emerging quantitative data suggest a role of disordered flanking regions, which could make multiple transient interactions with a folded interaction partner to either increase or decrease affinity. ,, Phylogenetic methods are powerful in pinpointing evolutionarily conserved regions in proteins. If these regions are involved in a protein–protein interaction, then the conserved residues are likely important for affinity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…This hydrophobic collapse can occur as a consequence of the increase in free energy or the increase in temperature, both of which results in a decrease in enthalpy. Such reduction in enthalpy has been shown to increase protein stability. , …”
Section: Discussionmentioning
confidence: 99%
“…Such reduction in enthalpy has been shown to increase protein stability. 90,91 Another interesting and important pattern in relation to the solvent accessibility and the change in conformational free energy can be observed. Although, on average, as conformations become more structured and less hydrophobic as the free energy increases (Figures 5, 6 and 8), the broader distribution of HI values suggests that a significant proportion of high free energy (in the 10−25 kJ/mol range) structured conformations retain a substantial hydrophobic character compared to those sampled at the lower free energy range (<10 kJ/mol) (Figure 8).…”
Section: Conformations With Predominantly α-Helical Content Appear Ne...mentioning
confidence: 91%
“…As mentioned, the full-length MeCP2 as well as their eGFP fusion variants were found to possess an abnormally large hydrodynamic radius for a globular protein of their size, consistent with previous studies [ 26 ]. Other work has shown that while the structured MeCP2 domains such as the MBD possess a radius consistent with that of globular protein, a MeCP2 protein construct that harbors this domain along with its disordered flanking regions, has a very significantly enlarged radius of 5.5 nm [ 29 ]. This further shows the degree of disorder that the random coil portions of MeCP2 impart on structured domains such as well as on the overall protein conformation.…”
Section: Discussionmentioning
confidence: 99%